Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.1002/bbb.2169
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of sweet sorghum genotypes for bioethanol yield and related traits

Abstract: The cultivation of sweet sorghum (Sorghum bicolor (L.) Moench) for bioethanol production is receiving global attention due to the plant's sugar‐rich stalk juice, which can be fermented directly to ethanol. One of the important steps toward the development of a superior sweet sorghum cultivar is proper assessment of bioethanol‐related traits in different environments. This study was conducted to characterize global sweet sorghum accessions for bioethanol yield and related traits. To do this and to obtain a fina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 40 publications
(50 reference statements)
0
10
1
Order By: Relevance
“…In this study, stalk residuals of Gebabe variety reducing sugar were not similar to the studies reported by Hunsigi et al [ 36 ], who reported highest reducing sugars were observed in RSSV 138 (14.78%) and the least reducing sugars were observed in NSSV 260 (11.35%) varieties of sweet sorghum. The range obtained was slightly lower than the findings of Batoul [ 37 ]; Guden et al [ 38 ] found a range of 9.19 to 18.47%. The highest reducing sugar of Chiquere variety was 18.3%, which is found in the range of the study reported by Sir Elkhatim [ 39 ], who found lowest and highest reducing sugar contents were 13.64 and 18.78%, respectively, in sweet sorghum.…”
Section: Discussioncontrasting
confidence: 71%
“…In this study, stalk residuals of Gebabe variety reducing sugar were not similar to the studies reported by Hunsigi et al [ 36 ], who reported highest reducing sugars were observed in RSSV 138 (14.78%) and the least reducing sugars were observed in NSSV 260 (11.35%) varieties of sweet sorghum. The range obtained was slightly lower than the findings of Batoul [ 37 ]; Guden et al [ 38 ] found a range of 9.19 to 18.47%. The highest reducing sugar of Chiquere variety was 18.3%, which is found in the range of the study reported by Sir Elkhatim [ 39 ], who found lowest and highest reducing sugar contents were 13.64 and 18.78%, respectively, in sweet sorghum.…”
Section: Discussioncontrasting
confidence: 71%
“…saccharatum (L.) Mohlenbr. ], a C4 crop with high photosynthetic efficiency (Almodares and Hadi, 2009), is used for animal feeding (Inal et al, 2021), and ethanol production (Guden et al, 2020), and is a drought and high-temperature tolerant species. High genetic variation for salt tolerance among sorghum genotypes that are generally tolerant to abiotic stresses such as drought and salinity was reported (Maiti et al, 1994;Rajabi Dehnavi et al, 2020).…”
Section: Orcid Id (By Author Order)mentioning
confidence: 99%
“…As a consequence, for BMP as for first‐generation ethanol production based on stem soluble sugars (Guden et al, 2020), there is a higher priority to mobilize alleles maximizing the soluble sugar content of the stem in the elite BMP varieties than to manipulate the cell wall composition. Nevertheless, analysis of midrib color variability, which is a proxy of the dry gene alleles (green (juicy) vs. white (dry)) whose impact on sugar yield has been confirmed (in Xia et al, 2018 but also in the present study ( p < 0.012)), in our panel, did not reveal a significant impact on the Biomethane potential ( p > 0.064).…”
Section: Discussionmentioning
confidence: 99%